The formation and development process of maritime security in armed conflicts - Махмурова-Дишлюк, Олена Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In today’s world, security is one of the most pressing. They affect almost all the important aspects of society - politics, economy and people’s welfare. From that how well the relevant government agencies operating in this area will depend on public safety, economic efficiency and competitiveness of transport, and finally - the weight and significance of the world’s states, which show real concern for the safety of their transport systems. One of the most important issues today is to define the theory and practice of maritime security in armed conflicts. This question has the status of an interdisciplinary, international as covers, criminal, and administrative theory of law. In armed conflicts at sea there is a risk of damage to vehicles and damage to property and the crew. This category is called "risk of shipping" as the likelihood of adverse effects of external interference in the crew for the purpose of taking possession of the vessel or cargo. The functioning of this category of causes of accidents - that is abnormal functioning of the mechanisms situations vessel. By type, the most common emergency events on the sea and river transport that occurred in 2015 in Ukraine are: invasions, damaged propeller steering complex, overturning, collision, overturning touch power lines, grounding, detection of low-quality diesel fuel, ice damage, pollution, failure of navigation equipment, steering gear, non-transport events (water leaks, flooding vessel, explosive detection, loss of soil sampling devices, fires, etc.) out to sea in between navigation from uncontrolled item without any rescue equipment without technical inspections on vehicles that are not re-registered the established order and not assigned to any base, parking and others. Moreover, it should be noted that the main causes of emergency events on the sea and river transport is primarily a basic violation of regulations governing relations in this sphere.